Relationship Between Nutritional Status and Severity of Pneumonia among Children Under Five - Rizone, Alifya Shifwah; Meirina, Fathia; Hamdi, Tasrif; Aldy, Fithria (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background. Pneumonia is known as a forgotten pandemic, leading to high morbidity and mortality, especially among children under five years, with nutritional status identified as a risk factor for the disease's incidence. This study aimed to determine the relationship between nutritional status and pneumonia severity in children under five. Methods. An analytical observational study with a cross-sectional design was conducted among 122 children aged 2-59 months diagnosed with pneumonia based on medical record data from Prof. Dr. Chairuddin Panusunan Lubis Medan Hospital from February 2022 - January 2024. The data were obtained with consecutive sampling. Data were analyzed through univariate and bivariate analyses using the chi-square test with SPSS software version 27. Results. Of 122 patients, the majority of patients were aged 12-59 months (64.8%), male (56.6%), had good nutritional status (63.1%), had a high level of life outcomes (98.4%), and had pneumonia (71.4%). Bivariate analysis showed a significant relationship between nutritional status and pneumonia severity (p < 0,001); PR = 4,3023; CI = 3,449 – 20,338). But there was no relationship between age (p = 0,081; PR = 1,740; CI = 0,989 – 4,963) and gender (p = 1,000; PR = 1,02; CI = 0,468 – 2,283) with severity of pneumonia. Conclusion. There is a significant relationship between nutritional status and severity of pneumonia in children under five. Keywords: Pneumonia, severity, nutritional status, severe pneumonia, children